How do we prove in propositional calculus :(adsbygoogle = window.adsbygoogle || []).push({});

......p^(qvr) <===> (p^q)v(p^r) semantically and syntactically

**Physics Forums - The Fusion of Science and Community**

# Proof of p^(qvr) <=> (p^q)v(p^r)

Know someone interested in this topic? Share a link to this question via email,
Google+,
Twitter, or
Facebook

Have something to add?

- Similar discussions for: Proof of p^(qvr) <=> (p^q)v(p^r)

Loading...

**Physics Forums - The Fusion of Science and Community**